Postsynaptic density protein transcripts are differentially modulated by minocycline alone or in add-on to haloperidol: Implications for treatment resistant schizophrenia. (April 2017) - Buonaguro, Elisabetta F; Tomasetti, Carmine; Chiodini, Paolo; Marmo, Federica; Latte, Gianmarco; Rossi, Rodolfo; Avvisati, Livia; Iasevoli, Felice; de Bartolomeis, Andrea
In this study, we investigated whether minocycline, a second-generation tetracycline proposed as an add-on to antipsychotics in treatment-resistant schizophrenia (TRS), may affect the expression of Homer and Arc postsynaptic density (PSD) transcripts, implicated in synaptic regulation. Minocycline was administered alone or with haloperidol in rats exposed or not to ketamine, mimicking acute glutamatergic psychosis or naturalistic conditions, respectively. Arc expression was significantly reduced by minocycline compared with controls. Minocycline in combination with haloperidol also significantly reduced Arc expression compared with both controls and haloperidol alone. Moreover, haloperidol/minocycline combination significantly affected Arc expression in cortical regions, while haloperidol alone was ineffective on cortical gene expression. These results suggest that minocycline may strongly affect the expression of Arc as mediated by haloperidol, both in terms of quantitative levels and of topography of haloperidol-related expression. It is noteworthy that no significant pre-treatment effect was found, suggesting that pre-exposure to ketamine did not grossly affect gene expression. Minocycline was not found to significantly affect haloperidol-related Homer1a expression. No significant changes in Homer1b/c expression were observed. These results are consistent with previous observations that minocycline may modulate postsynaptic glutamatergic transmission, affecting distinct downstream pathways initiated by N-methyl-D-aspartate (NMDA) receptor modulation, i.e. Arc-mediated but not Homer1a-mediated pathways.